A narrative review of neuroprotective effects of remifentanil: from basic research to clinical practice - Jiang, Xun; Wu, Meirong; Yan, Chenghui; Liu, Jia (Frontiers in Neurology, 2025)
Opioid receptor agonists constitute a class of pharmaceuticals that are extensively employed in anesthesia and analgesia. Remifentanil (RF), a novel synthetic opioid receptor agonist, is characterized by rapid onset of action and a short half-life, attributed to its unique pharmacokinetic profile. Clinically, RF is often used for total intravenous anesthesia. In recent years, RF has garnered more attention due to its potential organ-protective effects. This review aims to consolidate the existing evidence regarding the neuroprotective properties of RF, encompassing various levels ranging from molecular mechanisms to clinical applications. Experimental studies demonstrate that RF exerts protective effects in brain injury models, with its mechanisms being associated with the attenuation of apoptosis, oxidative stress, and neuroinflammation. In clinical practice, RF serves as a safe and effective analgesic regimen for patients with traumatic brain injury (TBI), those undergoing neurosurgical procedures, and individuals requiring endotracheal intubation; furthermore, it confers certain benefits to the recovery of patients' neurological function. Compared with fentanyl, RF is capable of reducing the incidence of delirium and postoperative cognitive dysfunction (POCD) in patients. Moreover, remifentanil-induced hyperalgesia (RIH) during clinical administration is also discussed. In conclusion, RF is an anesthetic agent with significant neuroprotective potential. Future research should focus on elucidating its precise mechanism of action, optimizing clinical administration regimens, and exploring strategies in RIH management.